Implementasi Sistem Coretax: Studi pada Klien KJA AW&L - Ferina Octaviana Sari Oding; Diah Hari Suryaningrum (Lembaga Pengembangan Kinerja Dosen, 2025)
The implementation of Coretax on taxpayers (clients) is able to provide an overview of how this application works and affects the taxpayer's compliance. This research aims to analyze the impact of Coretax application implementation on taxpayer compliance in AW&L Accounting Service Office (KJA) clients. The approach used in this research is descriptive qualitative. Collection of research data through literature studies, interviews and direct observations. Research results show that Coretax is able to simplify the tax reporting process through automation features, data integration, and comprehensive usage guidelines. The implementation of Coretax has a positive impact on taxpayer compliance. The obstacles found in the implementation of Coretax include low technology literacy, the need to provide additional education and training in the use of Coretax, and there are technical problems in the Coretax access system due to poor optimal signals. The improvement of the Coretax system by the Directorate General of Taxes is always updated in order to improve the tax administration system in Indonesia.